Repair using the pectoralis major musculocutaneous flap for refractory anastomotic leakage after total esophagectomy - Yoko Oga; Tomoyuki Okumura; Takeshi Miwa; Yoshihisa Numata; Shigeki Matsumoto; Koji Kaneda; Nana Kimura; Mina Fukasawa; Masakazu Nagamori; Kosuke Mori; Naoya Takeda; Kenta Yagi; et al. (Surgical Case Reports, 2023)
Abstract Background The pectoralis major musculocutaneous flap (PMMF) is a pedicled flap often used as a reconstruction option in head and neck surgery, especially in cases with poor wound healing. However, applying PMMF after esophageal surgery is uncommon. We report here, the case of a successfully repaired refractory anastomotic fistula (RF) after total esophagectomy, by PMMF. Case presentation A 73-year-old man had a history of hypopharyngolaryngectomy, cervical esophagectomy, and reconstruction using a free jejunal graft for hypopharyngeal carcinosarcoma at the age of 54. He also received conservative treatment for pharyngo-jejunal anastomotic leakage (AL), then postoperative radiation therapy. This time, he was diagnosed with carcinosarcoma in the upper thoracic esophagus; cT3rN0M0, cStageII, according to the Japanese Classification of Esophageal Cancer 12th Edition. As a salvage surgery, thoracoscopic total resection of the esophageal remnant and reconstruction using gastric tube via posterior mediastinal route was performed. The distal side of the jejunal graft was cut and re-anastomosed with the top of the gastric tube. An AL was observed on the 6th postoperative day (POD), and after 2 months of conservative treatment was then diagnosed as RF. The 3/4 circumference of the anterior wall of the gastric tube was ruptured for 6 cm in length, and surgical repair using PMMF was performed on POD71. The edge of the defect was exposed and the PMMF (10 × 5 cm) fed by thoracoacromial vessels was prepared. Then, the skin of the flap and the wedge of the leakage were hand sutured via double layers with the skin of the flap facing the intestinal lumen. Although a minor AL was observed on POD19, it healed with conservative treatment. No complications, such as stenosis, reflux, re-leakage, were observed over 3 years of postoperative follow-up. Conclusions The PMMF is a useful option for repairing intractable AL after esophagectomy, especially in cases with large defect, as well as difficulties for microvascular anastomosis due to previous operation, radiation, or wound inflammation.